2007
DOI: 10.1071/ah070s79
|View full text |Cite
|
Sign up to set email alerts
|

Supporting work practices, improving patient flow and monitoring performance using a clinical information management system

Abstract: Providing information technology solutions to clinicians to support their work practices benefits clinicians, administrators and patients. We present our 8-year experience with an inexpensive information management system which provides clinical and business process support for clinicians and bed managers. The system has been used by an area rehabilitation and aged care service to manage inpatient consultations and patient flow across nine hospitals. Performance monitoring of the time from referral to consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
12
2
Order By: Relevance
“…Another Australian study has also reported the waiting time for acute hospital patients assessed as ready for rehabilitation to be admitted – 67% were admitted within 1 day and 77% within 2 days, which was slightly better than our results. A study in Canada reported a relationship between shorter delays for transfer to rehabilitation and a shorter rehabilitation LOS .…”
Section: Discussioncontrasting
confidence: 82%
“…Another Australian study has also reported the waiting time for acute hospital patients assessed as ready for rehabilitation to be admitted – 67% were admitted within 1 day and 77% within 2 days, which was slightly better than our results. A study in Canada reported a relationship between shorter delays for transfer to rehabilitation and a shorter rehabilitation LOS .…”
Section: Discussioncontrasting
confidence: 82%
“…Use should be made of systems for the early identification 15 and referral of patients appropriate for rehabilitation 24 …”
Section: Proposals To Improve the Organisation And Delivery Of Rehabimentioning
confidence: 99%
“…5 In addition, this knowledge will set the baseline for examining the impact of any implemented change, 4 such as introduction of an electronic information system. [6][7][8] Furthermore, such details are important in informing public policy or managerial decision on staffing levels, 9 either for newly built aged care facilities or existing facilities in which resident case mix has changed.…”
Section: Introductionmentioning
confidence: 99%